2020
DOI: 10.3390/membranes10090201
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated Transport of Copper(II) across Polymer Inclusion Membrane with Triazole Derivatives as Carrier

Abstract: This study investigates copper(II) ion transport through a polymer inclusion membrane (PIM) containing 1-alkyl-1,2,4-triazole (n = 8, 9, 10, 11, 12, 14), o-nitrophenyl octyl ether as the plasticizer and cellulose triacetate as the polymer matrix. The feeding phase was a solution of 0.1 mol/dm3CuCl2 and an equimolar (0.1 mol/dm3) mixture of copper, nickel, and cobalt chlorides with varying concentrations of chloride anions (from 0.5 to 5.0 mol/dm3) established with NaCl. The receiving phase was demineralized wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…What is more, 1,2,4-triazoles and their amino derivatives have also been studied as extractants of Co(II), Ni(II), Zn(II) and Cd(II) ions [23]. Moreover, the effectiveness of removing Cu(II) [24] and Ni(II) [25] ions during SX with 1-alkyl-1,2,4-triazoles has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, 1,2,4-triazoles and their amino derivatives have also been studied as extractants of Co(II), Ni(II), Zn(II) and Cd(II) ions [23]. Moreover, the effectiveness of removing Cu(II) [24] and Ni(II) [25] ions during SX with 1-alkyl-1,2,4-triazoles has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Other carrier groups applicable to the removal of metal ions are calixarenes (e.g., Ulewicz and co-authors used a p-tert-butylcalix [4]arene derivative to transport Pb(II) ions across PIMs [19], whereas a calix [4]-crown-6-derivative nest carrier was used to recover Zn(II), Cd(II), and Pb(II) ions by a PIM membrane [20]). However, research on the recovery of different metal ions from aqueous solutions is not based solely on the search for new compounds (extractants and carriers); well-known compounds with relatively simple structures are increasingly being used for this purpose [21,22]. Lately, 2,6-diaminopyridine has been applied for the removal of copper(II) and zinc(II) ions from aqueous solutions in a polymer inclusion membrane and in a classic solvent extraction processes [23].…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the metal ion recovery rate strictly depends on the solution composition. Additionally, Gajda et al [5] demonstrated the possibility of separating non-ferrous metal ions via transport across polymer inclusion membranes containing derivatives of 1-alkyl-1,2,4-triazoles. The authors determined the conditions of Cu(II), Co(II) and Ni(II) ion separation through the membrane and showed that the transport rate of these metals depends on the membrane viscosity and the stability of the metal complexes with the ion carrier.…”
mentioning
confidence: 99%